Gambaran Kreativitas Figural Pada Siswa SMK Negeri 4 Kota Kupang - Maria Gregoriana Carvallo; Mariana Dinah Charlota Lerik; Marleny P. Panis (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
This study aims to explore the level of figural creativity in students of SMK Negeri 4 Kota Kupang. Figural creativity, which involves the ability to generate new ideas through drawings, was evaluated using the Torrance Tests of Creative Thinking (TTCT). This study used a quantitative descriptive method involving 60 students as samples. Data were collected through a figural test that assessed aspects of fluency, flexibility, originality, and elaboration. Results showed that most students were in the average creativity category (47%), with small differences based on gender and age. Male students tended to be more dominant in average creativity than females. Factors such as social environment and culture also influence students' creativity.